A hybrid system for groundwater denitrification using electrocoagulation and adsorption. (1st November 2019) - Ziouvelou, Athina; Tekerlekopoulou, Athanasia G.; Vayenas, Dimitris V.
Abstract: The treatment of nitrate-contaminated groundwater was studied using a hybrid system comprising an electrocoagulation unit and a zeolite adsorption reactor. In the electrocoagulation (EC) process, aluminum alloy electrodes were used in an undivided cell. Experiments in the laboratory-scale reactor were carried out in unregulated temperature conditions to treat synthetic groundwater solutions containing initial nitrate concentrations of 10–100 mg NO3 − -N·L −1 in batch mode and without using additional pH buffers. Various operating variables, such as applied current density (about 20 mA cm −2 to 80 mA cm −2 ), concentration of NaCl electrolyte (0.0–1.0 g L −1 ) and treatment time (up to 120 min), were tested for their effects on nitrate removal. Results showed that initial NO3 − -N concentration, current density and electrolyte concentration, play important roles in EC. For all initial NO3 − -N concentrations and current densities tested, the highest NO3 − -N removal rates (up to 2.374 g L −1 ·d −1 ) were achieved without additional electrolyte and/or with the lowest electrolyte concentration of 0.1 g L −1 . In these experiments, EC reduced NO3 − -N to below the standard limit of 10 mg L −1 after 10–60 min of electrolysis. A significant quantity of by-products, ammonium and dissolved aluminum, formed during the process, however these were successfully removed by zeolite adsorption in the post-treatment step. The electrochemical reactor using the specific anode/cathode combination and an environmentally-friendly post-treatment step such as zeolite adsorption, can be used to efficiently remove nitrate from groundwaters because of its high efficiency. Highlights: A hybrid system was developed for the denitrification of polluted groundwater. Electrocoagulation–EC with Al electrodes was applied to reduce nitrates to ammonium. High nitrate removal rates were recorded up to 2.282 g L −1 d −1 . An adsorption capacity of up to 0.46 mgNH4 + -N·g −1 was achieved by the zeolite. Dissolved Al concentrations fell below the permitted limit of 1 mg L −1